On the use of Fe(dpm)3 as precursor for the thermal‐CVD growth of hematite nanostructures. Issue 5 (17th January 2017) - Gasparotto, Alberto; Carraro, Giorgio; Maccato, Chiara; Barreca, Davide
Abstract : The iron(III) β‐diketonate Fe(dpm)3 (dpm = 2, 2, 6, 6‐tetramethyl‐3, 5‐heptanedionate) is investigated as precursor for the thermally‐assisted chemical vapor deposition (CVD) of hematite (α‐Fe2 O3 ) nanostructures. To this aim, the compound gas‐phase reactivity is first elucidated by in‐situ infrared spectroscopy both under N2 and N2  + O2 atmospheres. Subsequently, Fe(dpm)3 is tested in CVD experiments on various substrates, as a function of the growth temperature, to evaluate the precursor applicability in the preparation of diversified hematite ‐based materials, potentially addressing various technological end‐uses. In this study, relevant results concerning the gas‐phase behavior of Fe(dpm)3 and the compositional, structural, morphological, and optical properties of the resulting α‐Fe2 O3 deposits are presented and critically discussed.